Time Overrun in Construction Projects from the Perspective of Project Management Consultant (PMC) - Memon, Aftab Hameed; abdul Rahman, Ismail; abdullah, Mohd Razaki; Abdul Aziz, Ade Asmi (Journal of Surveying, Construction and Property, 2011)
Time Overrun is one of the most significant issues being faced by the construction industry today. There are various factors responsible for the time overrun which require serious attention to understand and address in order to achieve successful completion of projects on time. This is because time overrun has great impact to construction cost which can never be recovered. Thirty (30) large construction projects in Malaysia were identified facing Time Overrun during construction. Out of 30 projects, 17 (56.67%) projects were caused by 1-100 days time overrun, 5 (16.67%) projects in between 101 to 200 days, 5 (16.67%) projects 201 to 300 days whereas 3 (10%) projects were delayed for time period above 300 days. A structured questionnaire was conducted amongst personnel of project management consultants (PMC). The data was analyzed statistically to calculate the causes mean rank of time overrun. It also computed the level of agreement with Kendall‟s formula. Dominating factors affecting time overrun are cash flow & financial difficulties faced by contractors, contractor‟s poor site management, and inadequate contractor experience, shortage of site works and ineffective planning & scheduling. The results of this study will enhance the selection process of awarding construction job to the contractor. Keywords: Time Overrun, Causes of Time overrun, PMC, Malaysian Construction Industri